The Pengaruh Metode Inquiry Menggunakan Media Audio Terhadap Kemahiran Menulis Puisi Siswa Kelas VIII Madrasah Tsanawiyah Idris Bintan Tahun Pelajaran 2023/2024 - Legi Elfitra; Asromah; Ahada Wahyusari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Received: Revised: Accepted: Keywords: Inquiry, Audio, Poetry This study discusses the effect of the inquiry method using audio media on the poetry writiing skills of grade VIII students of Madrasah Tsanaeiyah Idris Bintan academic year 2023/2024. The aim of this study was to describe the effect of the inquiry method using audio media on the poetry writing skills of grade VIII students of the Madrasah Tsanawiyah Idris Bintan academic year 2023/2024. The method used in this research is a quantitative method.This type of research is experimental research with a one group pretest posttest design.This population in this study were class VIII students at the Madrasah Tsanawiyah Idris Bintan academic year 2023/2024 class VIII, a total of 57 students. The variables in this study consisted of independent variables, namely the inquiry method using audio media and the dependent variable namely students poetry writing skills. Data collection was carried. This variables in this study consisted of independent variables, namely the inquiry method using audio media and the dependent variable namely students poetry writing skills. Data collection was carried out by giving an initial test or pretest and posttest or posttest. the data were analyzed using descriptive statistics and non-parametric statistics with the help of the SPSS version 29 aplication. The results showed that average score was 73 in the pretest and 87 in the posttest. In the hypothesis testing using the wilcoxon tes, a sinificance value (2-tailed) was 0,001< 0,05, thus inquiry method using audio media has an effect on the poetry writing skills of grade VIII students of the Tanjungpinang state Madrasah Tsanawiyah Idris Bintan academic year 2023/2024.